PEMIKIRAN POLITIK ISLAM; Sebuah Tinjauan Sejarah Terhadap Arus Pemikiran Islam Klasik sampai Awal Abad ke 20 - Arfiansyah Arfiansyah (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2010)
This qualitative research discusses generally the development of Islamic political thoughts from classical period to the beginning of twentieth centuries. By describing various mainstreams in the political thoughts, the author argues that Islam does not offer a very specific political system, but it respects and and is adaptable to any system since it does not oppose the tenet of the religion.